A Case of Relapsing Polyarthritis Associated With Hidradenitis Suppurativa - Avinash Adiga MD; John Pixley MD (SAGE Publishing, 2016)
Hidradenitis suppurativa (HS) is a chronic, inflammatory follicular skin disease with recurrent skin nodules, sinus tracts, and scarring. We observed a case of HS associated with relapsing polyarthritis. On presentation the patient had a flare of polyarthritis with an increase in the number and size of pustular nodules. He has had similar episodes 1 to 2 times yearly subsiding with antibiotic treatment. Radiographs revealed erosions and demineralization. Symptoms improved following institution of anti-inflammatory and antibiotic therapy. HS is associated with several inflammatory conditions, and dysregulation in innate immunity may play an important role in etiopathogenesis. Spondyloarthritis/sacroiliitis is the most common joint manifestation in HS and mechanism(s) underlying arthropathy is unknown. Treatment of arthritis in HS is anecdotal.